2017
DOI: 10.4250/jcu.2017.25.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiac Functions in Children and Adolescents with Type 1 Diabetes

Abstract: BackgroundCardiac dysfunction in patients with type 1 diabetes (T1D) represents one of the serious complications. To evaluate the cardiac function in children with T1D by conventional echocardiography and tissue Doppler imaging (TDI).MethodsThe study included 40 T1D patients (age between 6 and 16 years) with > 5 years duration of diabetes and 42 healthy control children. The patients were subjected to clinical evaluation and laboratory investigations [glycosylated hemoglobin A1c (HbA1c), serum lipids and lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
2
4
1
Order By: Relevance
“…As epicardial fat has been shown to be a form of visceral adipose tissue, these authors suggested it to be a metabolic and cardiovascular risk factor. Left atrial diameter was significantly increased in accordance with Abd-El Aziz et al and Flachskampf et al [16,17]. They mentioned that an enlarged left atrium is a sign of increased left atrial pressure which has developed over time.…”
Section: Cardiac Dysfunction Is a Common Cause Of Morbidity And Morta...supporting
confidence: 73%
“…As epicardial fat has been shown to be a form of visceral adipose tissue, these authors suggested it to be a metabolic and cardiovascular risk factor. Left atrial diameter was significantly increased in accordance with Abd-El Aziz et al and Flachskampf et al [16,17]. They mentioned that an enlarged left atrium is a sign of increased left atrial pressure which has developed over time.…”
Section: Cardiac Dysfunction Is a Common Cause Of Morbidity And Morta...supporting
confidence: 73%
“…IVRT was also found to be elongated in our population, which, to the best of our knowledge, was never described in the literature concerning PVC in children. Its increase relates to early diastolic dysfunction in many diseases such as hypertrophic cardiomyopathy, arterial hypertension, or diabetes 21,22 In PVC children, it is the consequence of dyssynchronous contraction due to arrhythmia, which leads in a natural way to dyssynchronous relaxation. The dyssynchronous myocardial activation is seen not only when a premature beat occurs but also during sinus rhythm neighboring the premature contraction 23 .…”
Section: Discussionmentioning
confidence: 99%
“…They are mostly the leading cause of death among diabetic patients, representing 50% of the deaths related to this disease [ 27 ]. Diabetic cardiomyopathy is characterized by ventricular dysfunction originating from myocyte hypertrophy [ 71 , 72 ] and myocardial fibrosis [ 73 ]. The AGE–RAGE axis has been admitted as one of the contributing factors to this incompletely elucidated chronic complication ( Figure 4 ) [ 29 ].…”
Section: Ages and Their Implication In Chronic Complications Of Diabetes Mellitusmentioning
confidence: 99%